Nutritional Status of Patients on Maintenance Hemodialysis in a Tertiary Referral Hospital of Nepal - Maskey, Abhishek; Regmi, Yukta Narayan; Katuwal, Sushant (Medical Journal of Shree Birendra Hospital, 2017)
Introduction: Malnutrition is a common problem in hemodialysis patient, which is associated with increased mortality and morbidity. There is paucity of data regarding the nutritional status of patient on maintenance hemodialysis in developing countries. This study attempts to access nutritional status of patients on hemodialysis in tertiary referral hospital on western region of Nepal and correlate it with biochemical and laboratory parameters. Methods: A total of fifty patients on hemodialysis were evaluated. Nutritional assessment was made by Subjective Global Assessment (SGA) score, anthropometrics [Body Mass Index (BMI), Triceps Skin Fold Thickness (TSF), Mid Arm Circumference (MAC), Mid Arm Muscle Circumference (MAMC) and biochemical tests. Results: The study assessed 50 patients (34 males and 16 females) with mean age of 54 ± 14 years. Seventy eight percent (39) patients had mild to moderate malnutrition. Anthropometric parameters like BMI, TSF, MAC with normal nutrition were significantly higher than in patients with mild to moderate malnutrition. Malnutrition score (MS) by SGA significantly correlated with duration of dialysis. However, serum albumin was not statistically significant. Conclusion: Malnutrition is very common in patients undergoing hemodialysis with SGA having significant correlation with duration of dialysis. Routine nutritional monitoring among such patients are extremely important for diagnosing malnutrition early on, thus preventing complications and reducing the morbidity and mortality rates in this population.